ANALISIS PENGARUH KUALITAS PELAYANAN DAN KEPUASAN NASABAH TERHADAP PENINGKATAN DEBITUR PADA PT BPR PUNDHI KABUPATEN NGAWI - Antonik Putut Andria; Dwi Okta Meliyana; Eni Cahya Mastuti (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2013)
This study aims to identify and analyze the effect of service quality for increased customer satisfaction against the debtor on PT BPR Pundhi Ngawi district in 2012 and partially simultaneous. The population in this study is the whole debtor PT BPR Pundhi Ngawi district with a sample size of 100. The data analysis technique descriptively and quantitatively by linear regression method. Based on the quantitative analysis of the results showed that the quality of service, customer satisfaction increased significantly affect the debtor at PT BPR Pundhi Ngawi district. Keywords: Service Quality, Customer Satisfaction and Improved Debtor.